Plasma Levels of Free Fatty Acids in Women with Gestational Diabetes and Its Intrinsic and Extrinsic Determinants: Systematic Review and Meta-Analysis - Jose Rafael Villafan-Bernal; Mariana Acevedo-Alba; Rodrigo Reyes-Pavon; Guillermo Andres Diaz-Parra; Diana Lucia Lip-Sosa; Hilda Imelda Vazquez-Delfin; Martha Hernandez-Muñoz; Daniel Ely Bravo-Aguirre; Francesc Figueras; Raigam Jafet Martinez-Portilla (Journal of Diabetes Research)
Background. Free fatty acids, also known as nonesterified fatty acids, are proinflammatory molecules that induce insulin resistance in nonpregnant individuals. Nevertheless, the concentration of these molecules has not been systematically addressed in pregnant women. Objective. This meta-analysis is aimed at evaluating the difference in free fatty acid plasma levels between women with gestational diabetes and healthy pregnant controls and their intrinsic and extrinsic determinants. Methods. We performed a systematic search to find relevant studies published in English and Spanish using PubMed, SCOPUS, and ISI Web of Knowledge. We included observational studies measuring the mean plasma levels of free fatty acids among gestational diabetes and healthy pregnant women, with at least ten subjects being analyzed in each group. The standardized mean difference (SMD) by random effects modeling was used. Heterogeneity was assessed using Cochran’s Q, H, and I2 statistics. Results. Among the 290 identified studies, twelve were selected for analysis. A total of 2426 women were included, from which 21% were diagnosed as having gestational diabetes. There were significantly higher levels of free fatty acids among women with gestational diabetes (SMD: 0.86; 0.54-1.18; p<0.001) when compared to healthy pregnant controls and between-study heterogeneity (I2=91%). The metaregression analysis showed that the gestational age at inclusion was the only cofactor influencing the mean levels of free fatty acids, indicating a trend towards lower plasma levels of free fatty acids later in gestation (estimate: -0.074; -0.143 to -0.004; p=0.036). No significant publication bias was found nor a trend towards greater results in small studies. Conclusions. Women with gestational diabetes have higher levels of free fatty acids when compared to healthy pregnant controls. More investigation is needed to assess the potential role of free fatty acids in the prediction of gestational diabetes earlier in pregnancy.